Factors associated with premenstrual syndrome — A survey of new female university students. Issue 2 (3rd January 2013) - Cheng, Shu‐Hui; Shih, Chi‐Chen; Yang, Yen‐Kuang; Chen, Kow‐Tong; Chang, Yun‐Hsuan; Yang, Yi‐Ching
Abstract: Premenstrual syndrome (PMS) can impact an individual's interpersonal relationships, social interactions, productivity, lifestyle, school performance and emotional well‐being. This study was designed to explore the factors associated with PMS in new female university students in Taiwan. The test battery included a self‐administered structured questionnaire, the five‐item brief symptoms rating scale, the Pittsburgh Sleep Quality Index and the Chinese Premenstrual Symptom Questionnaire. Additionally, details of the participants' lifestyles and family and personal histories of physical illness were recorded. Serum lipids were also measured. Of all the participants (N = 1699), 39.85% were defined as having PMS. Using logistical regression analysis, we found a positive relationship between PMS and consuming more foods containing egg yolk, greater alcohol intake, poorer sleep quality, higher likelihood of psychiatric morbidity, family history of dyslipidemia, and a higher serum cholesterol level. The results show that PMS is prevalent among new female university students and that lifestyle and nutritional/metabolic factors may play a role in this disorder.